Experiential Marketing Management for Enhancing the Local Handwoven Textile Business Community in Sukhothai, Thailand: A UNESCO World Heritage - Tatnormjit, Taviz (International Review of Management and Marketing, 2026)
This study investigates experiential marketing management to enhance the local handwoven textile business community in Sukhothai, Thailand, a UNESCO World Heritage site and Creative City of Crafts and Folk Art. The objectives are (1) to analyze key components of experiential marketing management and (2) to propose developmental guidelines for local textile enterprises. A quantitative design was employed using a structured questionnaire with 460 consumers aged 20 and above in Sukhothai, Thailand, selected via convenience sampling. Data were analyzed using descriptive statistics and inferential techniques, including Confirmatory Factor Analysis, and Structural Equation Modelling. The results show that Business Management, Customer Behavior, and Experiential Marketing each have significant positive effects on Purchase Intention, while Business Management and Customer Behavior also significantly influence Experiential Marketing, supporting all hypothesized paths. Based on these findings, seven guidelines are proposed, focusing on integrating Schmitt’s experiential modules into retail environments, enhancing digital marketing for omnichannel engagement, and building community enterprise capacity aligned with Sukhothai’s UNESCO heritage identity. The study offers practical implications for community enterprises, tourism policymakers, and regional planners seeking to strengthen local economies and preserve intangible cultural heritage.